Monitoring Dual VEGF Inhibition in Human Pancreatic Tumor Xenografts With Dynamic Contrast-Enhanced Ultrasound. (14th February 2020) - Lamuraglia, Michele; Barrois, Guillaume; Le Guillou-Buffello, Delphine; Santin, Mathieu; Kerbol, Anne; Comperat, Eva; Coron, Alain; Lucidarme, Olivier; Bridal, S. Lori
Background: Association of drugs acting against different antiangiogenic mechanisms may increase therapeutic effect and reduce resistance. Noninvasive monitoring of changes in the antiangiogenic response of individual tumors could guide selection and administration of drug combinations. Noninvasive detection of early therapeutic response during dual, vertical targeting of the vascular endothelial growth factor pathway was investigated in an ectopic subcutaneous xenograft model for human pancreatic tumor. Methods: Dynamic contrast-enhanced ultrasound 12 MHz was used to monitor tumor-bearing Naval Medical Research Institute mice beginning 15 days after tumor implantation. Mice received therapy from 15 to 29 days with sorafenib (N = 9), ziv-aflibercept (N = 11), combined antiangiogenic agents (N = 11), and placebo control (N = 14). Sorafenib (BAY 43-9006; Nexavar), a multikinase inhibitor acting on Raf kinase and receptor tyrosine kinases—including vascular endothelial growth factor receptors 2 and 3—was administered daily (60 mg/kg, per os). Ziv-aflibercept (ZALTRAP), a high-affinity ligand trap blocking the activity of vascular endothelial growth factor A, vascular endothelial growth factor B, and placental growth factor was administered twice per week (40 mg/kg, intraperitoneally). Results: Functional evaluation with dynamic contrast-enhanced ultrasound indicated stable tumor vascularization for the control group while revealing significant and sustained reduction after 1 day of therapy in the combined group ( P = .007). There was no survival benefit or penalty due to drug combination. The functional progression-free survival assessed with dynamic contrast-enhanced ultrasound was significantly higher for the 3 treated groups; whereas, the progression-free survival based on tumor size did not discriminate therapeutic effect. Conclusions: Dynamic contrast-enhanced ultrasound, therefore, presents strong potential to monitor microvascular modifications during antiangiogenic therapy, a key role to monitoring antiangiogenic combining therapy to adapt dose range drug.